Has China entered a new era of Cross-border mergers and acquisitions? ------Examining the factors that influence its performance - Cui, Minjing (2008)
An increasing trend of China's cross-border mergers and acquisitions has attracted the interest of researchers and they have shown their concern on its effect on Chinese enterprises' performance. Hence this paper seeks to go deep into Chinese firms'cross-border M&As, find out the important factors that influence the success of acquisitions and thereby provides seniour managers in Chinese enterprises with managerial implications so that the firms can learn from it and gain better performance. This paper will provide a systematic overview of motivation, value creation, strategic management and cultural management, followed by a detailed case study interview with a middle manager from an auto firm in China. Through the findings, it has been found that the factors of motivations, value creations, cultural fit and strategic fit have great influence on the firm's choice of cross-border M&As and its performance as well. It also indicates the problem that may arise in the process of integration for senior managers to be aware of.